The relationship between job resources and core self-evaluations and work engagement among Generation Z employees in Indonesia - Nadya Isfahany Pasya; Zamralita Zamralita; Ismoro Reza Prima Prima (Priviet Social Sciences Journal, 2026)
Work Engagement (WE) is a crucial indicator of employee motivation, psychological health, and productivity. In Generation Z, engagement levels are often influenced by dynamic work conditions and the need for greater organizational support. Previous research indicates that WE is related to external factors, such as job resources, and internal factors, such as personal resources, including Core Self-Evaluations (CSE). Job resources encompass job elements that help individuals achieve goals and reduce job demands, whereas CSE reflects an individual's positive self-evaluation of their abilities, control, and emotional stability. Although both variables have been extensively researched, a deeper understanding of how they relate to WE among Generation Z employees in Indonesia is required. This study aimed to examine the relationship between job resources, CSE, and WE among Generation Z employees. This study used a quantitative correlational approach. Participants were recruited through purposive sampling, with the criterion being that they were Generation Z employees actively working in Indonesia. Data collection was conducted through an online survey using the Job Resources Scale, developed based on the Job Demands–Resources (JD-R) framework and the Core Self-Evaluations Scale (CSES) by Judge et al. (2003), and the Utrecht WE Scale (UWES-9) by Schaufeli et al. (2002). All measurement instruments had good internal consistency (α > 0.700). The number of participants in this study was 214. The results showed that job resources have a positive and significant relationship with WE, meaning that the higher the support and resources employees perceive, the higher their WE. Furthermore, CSE also showed a positive and significant relationship with WE, although the strength of this relationship was lower than that of job resources. These findings align with Hobfoll’s (2001) Conservation of Resources (COR) theory, which emphasizes the importance of external and internal resources in shaping WE. This study is expected to provide new insights for organizations in designing strategies to strengthen work resources and develop personal resources to increase WE among Generation Z employees.